IMPLIKASI KEBIJAKAN PENGAKATAN SEKRETARIS DESA MENJADI PEGAWAI NEGERI SIPIL BERDASARKAN PP NO. 45 TAHUN 2007 DI KECAMATAN WIRADESA KABUPATEN PEKALONGAN - Sri Pujiningsih; Ichsan Syuhudi; Siti Zulaekha (LPPM Universitas Pekalongan, 2012)
Policies village government secretary to the government employees regulated in Act Number 32 Year 2004 on Regional Government which in turn followed by the issuance of Government Regulation No. 45 Year 2007 regarding appointment of the Secretary of the Village government being government employees. Appointment of secretary of the village government into the government employees be automatic without passing Candidate government employees.The policy is the policy on the one hand is a must, as already mandated by the Act, but on the other hand the implementation implications for the organization of the village government. One was in the form of demands from government officials that the village of the government employees appointments are not just for the village government secretary only, but also followed the appointment of village government officials.